Living with drought: climate change perceptions, adaptation, and mitigation among farmers in rural Bangladesh - Mahedi, Md.; Pervez, A. K. M. Kanak; Ishida, Akira; Shaili, Shabrin Jahan; Nurnobi, Md. (Frontiers in Climate, 2026)
The paper presents a new behavioural model that collectively focuses on how the smallholder farmers in the drought-prone Barind Tract of Bangladesh perceive, mitigate, and adapt with the effects of climate change. A survey of 385 farm households was examined with the help of linear and ordinal logistic regression models to point out socioeconomic institutional determinants of these behavioural reactions. Findings indicate that 46 per cent of farmers (n = 177) had a moderate perception of climate change, which was related mostly to lowered soil fertility, water shortage and decreased crop production. Age, education, and income had a significant positive effect on climate awareness (R2 = 0.692, p < 0.001), whereas agricultural extension, livestock ownership, and peer-to-peer learning had a positive effect on adaptive and mitigative abilities. Conversely, the lack of financial capacity and lack of access to the markets hindered climate action. The main practices by farmers were crop diversification (79%), soil-water conservation (66%), use of organic fertilisers (78%), and management of residues (69%). The novelty of the study is that it summarises perception, adaptation and mitigation into one analytical model, which exposes the behavioural interrelationships that constitute resilience. The results also highlight the effectiveness of enhancing social learning in networks, financial, and mainstream climate-smart agriculture in supporting low-carbon adaptive food systems in semi-arid areas of South Asia.